Reading on Philippine culture and social life - Lardizabal , Amparo;Tensuan-Leogardo, Felicitas (Manila, Philippines : Rex Book Store, 1976)
Readings on Philippine Culture and Social Life makes it possible for students to sample quickly a wide range of basic literature in Philippine culture.
A return to the past by Alfredo R. Roces -- The Beginnings of Filipino society and culture by F. Landa Jocano -- Prehistoric foundations of contemporary Filipino culture and society by Robert B. Fox -- The Land and natural resources of the Philippines by Telesforo W. Luna Jr. -- The Filipino by Eufronio M. Alip --The Changing pilitical life of Filipinos by Cesar A. Cruz -- The Filipino family and society by Jacob S. Quiambao -- Our customs, belief and superstitions by Dr. Amparo S. Lardizabal -- The Religion of the Filipinos by Mercedes Grau Santamaria -- Philippine games by Maria G. Javier -- Philippine music by Felipe Padilla de Leon -- Filipino identity in folk dances by Rodrigo L. Villa Jr. -- Philippine architecture by Leonardo Concepcion -- Contemporary painting of the Philippines by Galo B. Ocampo -- Philippine literature by Maximo Ramos -- Education in the Philippines by Gregorio C. Borlaza -- Our paper culture by Francisco Araneta -- Culture : a solution to our problems by Felipe Padilla de Leon -- Scenic spots by Hilario S. Francia -- Looking ahead, an epilogue by Pura Santillan-Castrence
Keywords: CULTURE -- PHILIPPINES